2023
DOI: 10.1155/2023/7944733
|View full text |Cite
|
Sign up to set email alerts
|

Effects and Mechanisms of Fucoxanthin from Hizikia fusiforme on Inhibiting Tongue Squamous Cell Carcinoma Proliferation via AKT/mTOR-Mediated Glycolysis

Xiu Qiang Zhang,
Tao Yu Liu,
Lu Tao Zhang
et al.

Abstract: Fucoxanthin, a natural carotenoid, contains special ene bonds and 5, 6-mono-epoxide compounds in its molecule, which has physiological activities such as anticancer, antioxidant, anti-inflammatory, antiobesity, and antidiabetic. However, the anticancer actions and underlying mechanisms of fucoxanthin on oral cancer remain to be assessed. In this study, we used tongue carcinoma (CAL-27) cells to examine the effects and underlying mechanisms of fucoxanthin derived from Hizikia fusiforme on CAL-27 proliferation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Recent investigations have further demonstrated compound 32 as a potential anticancer lead against multiple carcinomas. Compound 32 facilitated apoptosis and downregulated MMP gene expression in tongue cancer cell lines (CAL-27) [ 194 ]. Additionally, it demonstrated antiproliferative properties against CAL-27 cell lines through alteration of glucose uptake and inactivation of protein kinase B/mammalian target of the rapamycin (Akt/mTOR) signaling pathway [ 195 ].…”
Section: Marine Algaementioning
confidence: 99%
“…Recent investigations have further demonstrated compound 32 as a potential anticancer lead against multiple carcinomas. Compound 32 facilitated apoptosis and downregulated MMP gene expression in tongue cancer cell lines (CAL-27) [ 194 ]. Additionally, it demonstrated antiproliferative properties against CAL-27 cell lines through alteration of glucose uptake and inactivation of protein kinase B/mammalian target of the rapamycin (Akt/mTOR) signaling pathway [ 195 ].…”
Section: Marine Algaementioning
confidence: 99%
“…The molecular mechanism may involve upregulation of cyclin−dependent kinase inhibitor protein expression and downregulation of one or more cyclin−dependent kinases [ 8 ]. Additionally, recent research indicated that fucoxanthin inhibits tongue cancer CAL−27 cell migration and invasion by inhibiting the expression of protein kinase B (AKT)/mechanistic target of rapamycin (mTOR) pathway components [ 9 ]. Similarly, fucoxanthin promotes apoptosis and autophagy in mouse cancer cells by reducing the phosphorylation of Akt, its downstream proteins, and apoptosis−related proteins; it also reduces DNA damage in normal cells and tumor cell metastasis and invasion by inhibiting chronic inflammation [ 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%